KERANGKA PENGATURAN PENGELOLAAN CSR TERPADU (Studi Kasus di Kota Jakarta) - Bani Pamungkas (Refleksi Hukum: Jurnal Ilmu Hukum, 2017)
The Jakarta Government has responsibility to improve the welfare and prosperity of the people and to preserve the function of the environment. This responsibility can not be done alone. Business and Community support is required. Jakarta Government issued Government Regulation Number 112 of 2013 regarding the Social and Environmental Responsibility of the Business Sector. This paper study was performed to evaluation of Governor Regulation No. 112 of 2013 and its proposed changes. This study uses a combination of research methods that combine legal research methods of normative and empirical. Empirical study was conducted by Modified Participatory Action Research method. At the analytical stage, a combination of juridical analysis with regulatory modeling is used. Efforts to encourage improvement of governance of TSLDU, 4 (four) aspects need to be addressed, namely (1) Provision of Information and Administration of TSLDU Administration using Web-based Information System; (2) integrating TSLDU Support with the Regional Development Planning and Budgeting System; (3) Expansion of TSLDU Scope; and (4) Developing a Collaborative TSLDU Scheme.